The early childhood educator professional development grant research and practice - Sutterby, John A. (Bingley, U.K. : Emerald, 2011)
The 15th volume of Advances in Early Education and Day Care focuses on the implementation of professional development for early childhood educators, describing a number of models for improving early childhood care. These models differ by setting, urban, rural, public, private, center and home based child care. These programs also differ by implementation model. Mentoring, workshops, online information and college courses are examples of how professional development was implemented. The systematic assessment of both the providers and the children described in these chapters will be of assistance for future research designers who are conducting large scale data collection and analysis. These chapters should serve as a way for policy makers to become informed about how best to expend scarce resources in the implementation of professional development. Increasing our knowledge of effective practices in professional development is an important factor in improving the outcomes for future generations of children. The collection of these chapters in one volume should provide future developers of professional development with a road map for what works and what might not be as effective.
Introduction : early childhood educator professional development / John A. Sutterby -- Policy implication of research on early childhood educator professional development / Michael L. Kamil -- The dosage of professional development for early childhood professionals : how the amount and density of professional development may influence its effectiveness / Sharon Landesman Ramey, Nancy A. Crowell, Craig T. Ramey, Cathy Grace, Nedaa Timraz, Louise E. Davis -- Readiness to change in communities, organizations, and individuals / Shira M. Peterson, Amy C. Baker -- Project REEL (Resources for Early Educator Learning) : the design and implementation of a state-wide professional development initiative for early childhood educators in diverse childcare settings / Sarah Jo Sandefur, Amye R. Warren, Anne Gamble -- Building professional development for urban public preschools : experiences and reflections / Joanne Roberts, Alice Frye, Mary Lu Love, Lisa Van Thiel -- Effects of quality improvement system on early childhood education practitioners / Jianping Shen, Xin Ma, Wendy Tackett, Xuejin (Kim) Lu, Karen Brandi, Jeff Goodman, Lance Till, Grace Watson -- Professional development : change we can believe in / Maria Magdalena Aguilar-Crandall, John A. Sutterby.
Includes index.
Keywords: Education -- Elementary; Education -- Professional Development; Schools; Teaching staff; Early childhood education